Education and Mental Health: Causal Effects and Intra-Family Spillovers - Mustafa Özer; Jan Fidrmuc (CESifo GmbH, 2024)
Mental health is essential for well-being and quality of life. Yet, our knowledge of the determinants of mental health is limited. We analyze the impact of education on mental health using survey data on self-reported health of Turkish women. To deal with the potential endogeneity, we rely on a natural experiment: an increase in the compulsory education from 5 to 8 years in 1997. The results suggest that education has a favorable effect on mental health, physical health, and being target of abusive behavior. We specifically consider intra-family spillovers, which are important: husband's education has favorable effects on the wife's mental health, and both parents' educational attainments improve mental health of children. We account for the implications of assortative mating whereby the spouses' educational attainment are correlated. We show that each spouse's education has a favorable impact on women's mental health, but the effect of husbands' education dominates that of wives' education. These effects are particularly pronounced among women who grew up in low-income provinces and in families without history of childhood abuse.
Keywords: H51; H52; I12; I26; 330; health; mental health; education; instrumental variable; natural experiment